Effect of different salinity on the growth performance and proximate composition of isolated indigenous microalgae species - Noorazilah Haris (Elsevier, 2022)
The suitable culture condition for specific microalgae species is vitally important for their optimal growth and biochemical production. Therefore, this study emphasized on the isolation and screening of indigenous microalgae species with high growth performance from Setiu wetlands, Terengganu, Malaysia. Successfully isolated microalgae were identified based on morphological and molecular approaches using 18S rDNA technique. Microalgae were screened to identify their species with high growth performance based on optical density and Nile red fluorescence dye. Further, the effect of different salinity towards the growth performance of isolated microalgae and proximate composition including protein, lipid, and carbohydrate were identified. Out of nine microalgae strain, three species of indigenous microalgae were successfully isolated and identified known as Chlorella vulgaris, Tetraselmis chuii, and Isochrysis galbana during 16 days of culture period. The highest optical density was found in C. vulgaris, T. chuii, and I. galbana with 1.228 ± 0.039 a.u, 0.758 ± 0.024 a.u and 0.853 ± 0.048 a.u, respectively. Chlorella vulgaris, T. chuii, and I. galbana were also showed the highest specific growth rate with 0.548 μmax/day, 0.686 μmax/day and 0.478 μmax/day, respectively. Using Nile red fluorescent dye screening, C. vulgaris, T. chuii and I. galbana also showed the highest fluorescence intensity of lipid, carotenoid and chlorophyll a content. Based on these criteria, C. vulgaris, T. chuii and I. galbana were selected for further determination on the effect of salinity towards the growth and proximate composition of the selected microalgae. The optimum salinity level of culture medium for T. chuii was 40 ppt with the highest cell density (6.215 × 106 cells/mL; Day 6), protein content (40.47 ± 0.51% of dry weight) and carbohydrate content (42.57 ± 0.83% of dry weight). For I. galbana, 24 ppt was found to be the best culture medium in term of the highest cell density (20.58 × 106 cells/mL; Day 7), and carbohydrate content (29.28 ± 0.47% of dry weight), while lipid content was highest at 40 ppt (15.68 ± 0.58% of dry weight). For C. vulgaris, 10 ppt was the best culture medium in term of the highest cell density (31.17 × 106 cells/mL) and lipid content (13.12 ± 1.12% of dry weight), while carbohydrate and protein content were highest at 0 ppt with 44.53 ± 0.56% and 40.16 ± 2.22% of dry weight, respectively. Overall, the variation of salinity had affected the growth and biochemical compositions of C. vulgaris, T. chuii and I. galbana. Therefore, this study is important for the cultivation of C. vulgaris, T. chuii and I. galbana of different specific target by manipulating the salinity variation of culture medium that can be used as a feed in aquaculture industry.